Enhancing Soil Stability: The Impact of Rice Husk Ash on Expansive Soil Behavior - Rahaja Nikita; Kumar Gupta Ashok; Kanwar Kushal (E3S Web of Conferences)
Expansive soils, such as black cotton soils, are characterized by their pronounced vulnerability to swelling and shrinking caused by fluctuations in moisture levels. Such activity gives rise to worries over the longevity of constructions constructed on such soils, as they frequently undergo substantial expansion and contraction. Road surfaces, whether paved or unpaved, built on these expansive soil subgrades often experience problems such as potholes, cracking, wheel path rutting, heave and differential settlements Furthermore, apart from the difficulties presented by expanding soils, there is an escalating global issue with the proper management of waste materials produced by diverse operations. These waste materials not only exacerbate significant environmental problems but also require extensive acreage for proper disposal. Among the waste materials generated by the combustion husk of rice is rice husk ash (RHA). The incorporation of RHA as an additive in expansive soils might effectively mitigate their swelling and shrinkage characteristics, while simultaneously tackling the environmental and disposal issues linked to the ash. The present work reports, the findings of an empirical inquiry undertaken to examine the influence of RHA on the compaction, shrinkage, and swelling properties of expansive soil. Various amounts of RHA were mixed with soil in the study, and tests including Atterberg limit, free swell index, light compaction, California bearing ratio and unconsolidated undrained triaxial compression tests were conducted. The findings indicate that introducing RHA in suitable ratios not just significantly decreases the shrinkage and swelling characteristics of expansive soil but aa well as improves its stability